2018
DOI: 10.1080/07036337.2018.1513500
|View full text |Cite
|
Sign up to set email alerts
|

United in diversity? Europarties and their individual members’ rights

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Europarties are easily perceived as being part of the 'Brussels bubble' that should do more to reach out to civil society and citizens (Van Hecke et al, 2018). Europarties have introduced membership for individuals, but in her pioneering study, Hertner (2019) showed that Europarties had only very small numbers of individual members, with national member parties often against giving individual members stronger participation rights. Europarties face the challenge of scale: even democratic innovations such as deliberative panels or various online platforms cannot bring all citizens or party members across Europe together.…”
Section: Eu Constitutional Reforms Party Politics and Accumulated Exp...mentioning
confidence: 99%
“…Europarties are easily perceived as being part of the 'Brussels bubble' that should do more to reach out to civil society and citizens (Van Hecke et al, 2018). Europarties have introduced membership for individuals, but in her pioneering study, Hertner (2019) showed that Europarties had only very small numbers of individual members, with national member parties often against giving individual members stronger participation rights. Europarties face the challenge of scale: even democratic innovations such as deliberative panels or various online platforms cannot bring all citizens or party members across Europe together.…”
Section: Eu Constitutional Reforms Party Politics and Accumulated Exp...mentioning
confidence: 99%
“…It is thus not reasonable to expect that these parties will strengthen the participatory links with their members without any formal demands tied to authorization or funding. The main exception among the existing parties is the Alliance of Liberals and Democrats for Europe Party (ALDE), which ‐ because of ideological reasons ‐ has actively worked to build a membership base of individual citizens, also granting members rights in the party's internal decision‐making process (Hertner, 2019; Wolfs and Van Hecke, 2019, p. 273).…”
Section: European Party System Governance and Eu Democracymentioning
confidence: 99%
“…The EU regulatory framework contains detailed provisions on the required administrative and financial organization, and the responsibilities of the governing bodies. However, with regard to individual members and their rights, the rules are far more ambiguous (see also Hertner, 2019, pp. 4–5) and contain no minimum standards relating to involvement of members in the internal decision‐making procedures.…”
Section: European Party System Governance and Eu Democracymentioning
confidence: 99%
See 1 more Smart Citation
“…Given that even the biggest Europarties have far fewer resources than even their smallest member-parties and they also lack a mass direct membership (although see Hertner, 2018), they can be understood first and foremost as agents of national political parties (Bardi and Calossi, 2009). Thus, their standing hinges primarily on them delivering coordinating and informationsharing services to their membership.…”
Section: Europarties In Eu Politicsmentioning
confidence: 99%